2013
DOI: 10.2298/avb1303255n
|View full text |Cite
|
Sign up to set email alerts
|

Monthly and seasonal evaluation of dietary nutrients and their relationships with blood and milk parameters in lactating dairy cows

Abstract: Monthly and seasonal variations among dietary, blood and milk parameters and their interrelationships were investigated during the lactation period in Holstein dairy cows in order to determine reliable dietary indices that could be useful in the studies related to milk yield improvement. Samples were prepared monthly, up to 11 months of lactation and were analyzed by the current laboratory methods using appropriate kits. Mean monthly and seasonal comparison of the dietary, blood and milk values were diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The significant and positive correlations between serum TP and MP (r=0.452), as well as between serum albumin and MP (r=0.449) obtained in our studies show a clear metabolic and structural relationship between blood and milk proteins. The significant and positive correlation between total serum protein and milk protein was also noted by other authors on the level r=0,23, (p<0.01), but they did not compare albumin, specifically (Nozad et al, 2012). Other authors reported that they compared serum albumin with milk protein with insignificant result (r=0.107), but they tested cows in different lactation periods with different statuses (Djokovic et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The significant and positive correlations between serum TP and MP (r=0.452), as well as between serum albumin and MP (r=0.449) obtained in our studies show a clear metabolic and structural relationship between blood and milk proteins. The significant and positive correlation between total serum protein and milk protein was also noted by other authors on the level r=0,23, (p<0.01), but they did not compare albumin, specifically (Nozad et al, 2012). Other authors reported that they compared serum albumin with milk protein with insignificant result (r=0.107), but they tested cows in different lactation periods with different statuses (Djokovic et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…These relationships may also apply to milk, where our results showed significant positive correlations between serum Mg and MP, and, as a consequence, significant positive correlations between serum Mg and FDM. Interestingly, in other studies performed during different lactation periods in cows, other authors recorded a significant positive correlation between blood magnesium and blood protein at r=0.36 (p <0.01), but did not record a significant correlation between serum magnesium and protein in milk (Nozad et al, 2012). However, in other studies of cows, also during various lactation periods, there were no significant correlations between magnesium and serum protein or between magnesium and serum albumin, and also none between serum magnesium and protein in milk (Djokovic et al 2019).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation